Immobilization of purple non-sulfur bacteria to remove inorganic nutrients from aquarium system - Lee, Kar Chun (2015)
The aim of this experiment is to determine the suitability between two substrates which were agar substrates and coral rubbles that immobilized with Purple Non Sulfur bacteria (PNSB) and it was coded as FWS-KC1. Two experiments were conducted where the first experiment was isolation and purification of PNSB and followed by aquarium trial with two treatments which were immobilization of bacteria on agar substrates and coral rubbles. The first experiment which was isolation and purification of bacteria was started with isolation of bacteria from waste water ponds and natural pond around ""Universiti Malaysia Sabah"". After the isolation of PNSB, it was incubated under anaerobic condition where the light intensity was maintained at 2.5 klux and temperature was maintained at 30±2°c and the incubation period of PNSB was a week. The culture media that used was 112 media. Several analyses have been carried out to test on this strain of bacteria (FWS-KC1) which were in terms of dry cell weight and the highest production was 1.9267 g/L (day 6), carotenoid was 2.2603 mg/g (day 3) and for bacteriochlorophyll, the maxima absorption were 376, 379, 494, 524, 805, 864 nm. In addition, some simple biochemical tests were carried out such as anoxygenic and oxygenic test, motility test, salinity test, gram staining and microscopic viewing. Conclusion has been drawn out that FWS-KC1 was gram negative bacteria which were able to move around (motile) and it was classified in the group of Rhodopseudomonas. For second experiment, aquarium trial has been carried out to determine concentration of ammonia, nitrite, nitrate and phosphate. Two treatments were used to determine the suitability to immobilize PNSB. Another conclusion can be drawn out that, Immobilized bacteria on agar substrates was not suitable to reduce nitrogenous compound in aquarium water because the concentration of ammonia (2.4390 mg/l) was the highest (day 6) and concentration of phosphate (0.1398 mg/l) was low.